Effect of Audiovisual as an Educational Medium to Increase Knowledge and Participation in Acetic Acid Visual Inspection Examination (IVA) - Anis Nikmatul Nikmah; Dhita Kris Prasetyanti; Fithri Rif’atul Himmah (Universitas STRADA Indonesia, 2022)
Cervical cancer is the uncontrolled growth of abnormal cells in the cervix or cervix and is classified as a malignancy that can be diagnosed early, one of which is by carrying out an IVA examination. Lack of knowledge is one of the factors that causes a lack of participation in carrying out IVA examinations. The purpose of this study was to determine the effect of audiovisual as an educational medium to increase knowledge and participation in VIA examinations in WUS. The research design is a pre-experimental study with a one group pre test – post test research design. The population studied was all WUS who had had sexual intercourse in the corner village of RT 7 with a sample taken of 32 people using purposive sampling technique. The analysis used was univariate and bivariate analysis with the Wilcoxon test. The results of the study obtained ρ value (0.000) ˂ α = (0.05) so that H0 was rejected and H1 was accepted meaning that there is an Audiovisual Effect as an educational medium to increase knowledge and IVA Examination Participation in WUS. Based on the results of educational media research through audiovisuals, it increases the enthusiasm of WUS to participate in counseling and is easier to understand so that the implementation of counseling on continuous IVA examinations so that all WUS who have not yet carried out early detection of cervical cancer have awareness to be detected.